A transparent POE white EVA co-extruded film and preparation method thereof
By adding epoxy double-bonded structure compounds with specific crosslinking agents to the white EVA film, a transparent POE white EVA coextrusion film with high crosslinking is formed, which solves the corrosion of the white EVA film in high temperature and high humidity environment. The problem and the problem of low crosslinking achieve effective neutralization of acetic acid and protection of the battery cells.
Patent Information
- Application Number
- CN202310004420.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-03
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-01-03
AI Technical Summary
The existing white EVA film is prone to corrode the battery cells under high temperature and high humidity environments. In conventional solutions, inorganic alkali neutralizes acetic acid and produces metal ion residues, which affects the stability of the component and has low crosslinking leading to the risk of acetic acid precipitation.
Using a transparent POE white EVA coextruded film, a high crosslinking film is formed by adding epoxy compound with double bond structure to the white EVA layer and aid crosslinking agent dipentaerythritol pentaacrylate or dipentaerythritol hexaacrylate. Barrier acetic acid and neutralize acetic acid in a weak acid system to avoid bubble generation.
A high crosslinking film is achieved, and no bubbles are generated after long-term aging, which avoids corrosion of acetic acid on the battery cell, and has low power attenuation, meeting the 6-month shelf life requirement.
Smart Images

Figure BDA0004035667180000061 
Figure BDA0004035667180000062 
Figure BDA0004035667180000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesive films, and in particular to a transparent POE white EVA co-extruded film and a preparation method thereof. Background Art
[0002] With the development of battery technology, people have found that TOPCON technology has higher power generation efficiency than PERC. However, tests have found that the front of TOPCON batteries has the same PID problem as the back of PERC batteries. TOPCON batteries that use POE on the front and EVA on the back also have the problem of PID failure. This is because the EVA on the back will partially degrade and release VA under high temperature and humidity. VA will flow from the surrounding areas of the battery cell to the front, thereby affecting the power generation efficiency of the front. In order to increase the power generation power of the component, the EVA on the back is usually made white to increase the utilization rate of light by reflecting light. However, titanium dioxide will promote the degradation of EVA, making the white EVA film more likely to corrode the battery cell.
[0003] With the iteration of technology, there are more and more types of components. In order to increase the power generation capacity of the components, conventional components on the market usually use white film on the back to increase the reflectivity and light utilization rate. However, due to the high cost and weak adhesion of white POE film, white EVA film is usually used. However, white EVA film is easy to produce acetic acid under the catalysis of titanium dioxide, which can easily corrode the battery cells and solder strips. Especially with the iteration of technology and the update of battery cells, in order to reduce the corrosion of acetic acid to the battery cells, the film factory needs to add a layer of POE on the white EVA film to prevent the corrosion of acetic acid molecules to the battery cells or solder strips.
[0004] However, the current white EP structure only uses POE to isolate acetic acid, which does not solve the problem at the source. As the components are used in high temperature and high humidity environments for a long time, there is still a risk of acetic acid penetrating through POE. The current solution on the market is to add inorganic bases to acetic acid to neutralize the acetic acid, but inorganic bases will produce metal ion residues, affecting the stability of the components.
[0005] CN108794870B discloses a white photovoltaic encapsulation material for preventing whitening, and a preparation method and application thereof. The raw materials of the white photovoltaic encapsulation material include a main resin and the following components in percentage by mass of the main resin: 0.5-0.8% of a main cross-linking agent, 0.3-0.8% of an auxiliary cross-linking agent, 0.2-0.5% of a light stabilizer, 0.1-0.3% of a coupling agent, 0.1-0.3% of an antioxidant, and 3-8% of a white filler. The melting point of the main resin is 15-30 g / 10 min, and the main cross-linking agent is tert-butyl peroxyisobutyrate. Under the action of tert-butyl peroxyisobutyrate, the white photovoltaic encapsulation material can rapidly cross-link the main resin with a melting point of 15-30 g / 10 min, so that the encapsulation material is cross-linked and solidified before flowing to the front of the battery cell, preventing whitening, and preventing the prepared battery cell from generating hidden cracks, and ensuring a high power generation efficiency and reducing production costs. However, the film still has the problem of acetic acid precipitation when used in a high temperature and high humidity environment for a long time.
[0006] Therefore, it is necessary to develop an adhesive film with high cross-linking degree, low power attenuation and prevention of acetic acid precipitation and a preparation method thereof. Summary of the invention
[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a transparent POE white EVA co-extruded film and a preparation method thereof. The film prepared by the present invention has a high degree of cross-linking, does not generate bubbles after long-term aging, and avoids the corrosion problem of acetic acid precipitation on battery cells.
[0008] One of the purposes of the present invention is to provide a transparent POE white EVA co-extruded film. To achieve this purpose, the present invention adopts the following technical solutions:
[0009] A transparent POE and white EVA co-extruded film comprises a transparent POE layer and a white EVA layer formed by co-extrusion, wherein the transparent POE layer comprises a co-crosslinking agent, wherein the co-crosslinking agent comprises dipentaerythritol pentaacrylate and / or dipentaerythritol hexaacrylate, and the white EVA layer comprises an epoxy compound with a double bond structure.
[0010] The transparent POE white EVA co-extruded film of the present invention innovatively proposes to add a layer of transparent POE on the white EVA to block VA from directly corroding the battery cell, and at the same time solves the problems of low cross-linking degree of transparent POE white EVA, POE degradation to generate bubbles after wet heat aging, and large VA precipitation through formula adjustment.
[0011] Since POE is a non-polar material and EVA is a polar material, when the two materials are co-extruded together, they form a layer of non-polar material and a layer of polar material. The cross-linking aid used in the film is very polar, usually TAIC, so the cross-linking aid in POE can easily migrate into EVA, resulting in a reduction in the amount of the cross-linking aid in POE after being stored for a period of time, and an unqualified cross-linking degree of less than 60%, which cannot meet the requirement of a shelf life of 6 months. The present invention selects one or two of the cross-linking aids dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate to replace TAIC as the cross-linking aid. Since they have a large molecular weight and are difficult to precipitate, they are not easy to migrate into EVA, and have a good cross-linking degree under the same lamination conditions, with a cross-linking degree greater than 80%.
[0012] EVA easily releases acetic acid under high temperature and high humidity, causing acid corrosion of the battery cell. Conventional EVA film is neutralized by adding inorganic bases, but inorganic bases are usually highly alkaline and are not suitable for organic reactions, and will cause inorganic residues, resulting in a decrease in the volume resistivity of the film and a decrease in insulation performance, which poses a risk to the long-term aging performance of the component. Therefore, in the present invention, an epoxy compound with a double bond structure is added, the double bond reacts in the EVA resin, the epoxy opens the ring in a weak acid system, reacts with acetic acid to form an ester, neutralizes the acetic acid, and solves the problem of acetic acid corrosion.
[0013] In the present invention, the epoxy compound with a double bond structure comprises 4-vinyl epoxycyclohexane and / or (3,4-epoxycyclohexyl) methyl acrylate.
[0014] In the present invention, the transparent POE layer comprises the following components in parts by weight:
[0015] The weight proportion of POE is 97.4-98.9 parts.
[0016] The weight portion of the main cross-linking agent is 0.5-1 part, for example, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, 1 part, etc.
[0017] The weight portion of the auxiliary cross-linking agent is 0.4-0.8 parts, for example, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, etc.
[0018] The weight portion of the coupling agent is 0.1-0.5 parts, for example, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, etc.
[0019] The weight portion of the antioxidant is 0.1-0.3 parts, for example, 0.1 parts, 0.2 parts, 0.3 parts, etc.
[0020] Wherein, the auxiliary cross-linking agent comprises dipentaerythritol pentaacrylate and / or dipentaerythritol hexaacrylate.
[0021] The main cross-linking agent is a peroxide cross-linking agent, preferably tert-butyl peroxide-2-ethylhexyl carbonate (TBEC).
[0022] The coupling agent is preferably silane coupling agent KH570.
[0023] Preferably, the antioxidant is 770.
[0024] In the present invention, the white EVA layer comprises the following components by weight percentage:
[0025] The weight parts of EVA are 86.9-93.0 parts, for example, 86.9 parts, 87 parts, 88 parts, 89 parts, 90 parts, 91 parts, 92 parts, 93 parts, etc.
[0026] The weight proportion of titanium dioxide is 5-10 parts, for example, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, etc.
[0027] The weight portion of the main cross-linking agent is 0.5-1 part, for example, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, 1 part, etc.
[0028] The weight portion of the auxiliary cross-linking agent is 0.3-0.8 parts, for example, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, etc.
[0029] The weight portion of the coupling agent is 0.1-0.5 parts, for example, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, etc.
[0030] The weight portion of the antioxidant is 0.1-0.3 parts, for example, 0.1 parts, 0.2 parts, 0.3 parts, etc.
[0031] The epoxy compound with a double bond structure is 0.1-0.5 parts, for example, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, etc.
[0032] The main cross-linking agent is a peroxide cross-linking agent, preferably tert-butyl peroxide-2-ethylhexyl carbonate (TBEC).
[0033] The auxiliary cross-linking agent is triallyl isocyanurate (TAIC).
[0034] Preferably, the coupling agent is preferably silane coupling agent KH570.
[0035] Preferably, the antioxidant is 770.
[0036] The second object of the present invention is to provide a method for preparing the transparent POE white EVA co-extruded film described in the first object, comprising the following steps: co-extruding POE and EVA according to a ratio, and obtaining the transparent POE white EVA co-extruded film after irradiation.
[0037] The energy of the irradiation is 15-35kgy, for example, 15kgy, 16kgy, 17kgy, 18kgy, 19kgy, 20kgy, 21kgy, 22kgy, 23kgy, 24kgy, 25kgy, 26kgy, 27kgy, 28kgy, 29kgy, 30kgy, 31kgy, 32kgy, 33kgy, 34kgy, 35kgy and the like.
[0038] Preferably, the irradiation voltage is 300-500kv, for example, 300kv, 350kv, 400kv, 450kv, 500kv, etc.
[0039] Preferably, the irradiation speed is 40-60 m / min, for example, 40 m / min, 45 m / min, 50 m / min, 55 m / min, 60 m / min, etc.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] The adhesive film prepared by the present invention has a high cross-linking degree, and will not generate bubbles after long-term aging, thereby avoiding the problem of corrosion of the battery cell by acetic acid precipitation. Specifically, the initial cross-linking degree of the prepared adhesive film is 85.11-89.93%, the cross-linking degree after storage for 6 months is 81.57-85.03%, the power attenuation after DH1000H is 1.27-1.95%, and the battery cell after DH1000H is good and does not turn black. DETAILED DESCRIPTION
[0042] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0043] Unless otherwise specified, various raw materials of the present invention can be purchased from the market or prepared according to conventional methods in the art.
[0044] Example 1
[0045] The transparent POE and white EVA co-extruded film of this embodiment includes a transparent POE layer and a white EVA layer formed by co-extrusion.
[0046] By weight, the transparent POE layer comprises the following components:
[0047]
[0048] The auxiliary cross-linking agent is dipentaerythritol pentaacrylate;
[0049] The white EVA layer comprises the following components by weight percentage:
[0050]
[0051] The preparation method of the transparent POE white EVA co-extruded film of this embodiment comprises the following steps: co-extrude POE and EVA according to a ratio, and after irradiation, the irradiation energy is 25kgy, the irradiation voltage is 400kv, and the irradiation speed is 50m / min to obtain a transparent POE white EVA co-extruded film.
[0052] Example 2
[0053] The difference between this embodiment and embodiment 1 is that in the transparent POE, dipentaerythritol pentaacrylate is replaced by dipentaerythritol hexaacrylate, and in the white EVA, (3,4-epoxycyclohexyl)methyl acrylate is replaced by 4-vinylepoxycyclohexane.
[0054] Example 3
[0055] The transparent POE and white EVA co-extruded film of this embodiment includes a transparent POE layer and a white EVA layer formed by co-extrusion.
[0056] By weight, the transparent POE layer comprises the following components:
[0057]
[0058] The auxiliary cross-linking agent is dipentaerythritol pentaacrylate;
[0059] The white EVA layer comprises the following components by weight percentage:
[0060]
[0061]
[0062] The preparation method of the adhesive film of this embodiment is the same as that of the embodiment.
[0063] Example 4
[0064] By weight, the transparent POE layer comprises the following components:
[0065]
[0066] The auxiliary cross-linking agent is dipentaerythritol pentaacrylate;
[0067] The white EVA layer comprises the following components by weight percentage:
[0068]
[0069] The method for preparing the adhesive film of this embodiment is the same as that of embodiment 1.
[0070] Comparative Example 1
[0071] The difference between this comparative example and Example 1 is that in the transparent POE, dipentaerythritol pentaacrylate is replaced by TAIC, and the rest is the same as that of Example 1.
[0072] Comparative Example 2
[0073] The difference between this comparative example and Example 1 is that no (3,4-epoxycyclohexyl) methyl acrylate is added to the white EVA, and the reduced amount of (3,4-epoxycyclohexyl) methyl acrylate is added to other components on average to ensure that the total amount remains unchanged. The rest is the same as in Example 1.
[0074] Comparative Example 3
[0075] The difference between this comparative example and Example 1 is that in the white EVA, methyl acrylate (3,4-epoxycyclohexyl) is replaced by an equal amount of magnesium hydroxide, and the rest is the same as that of Example 1.
[0076] The performance of the films prepared in Examples 1-4 and Comparative Examples 1-3 was tested, and the test results are shown in Table 1.
[0077] Table 1
[0078]
[0079] As can be seen from the data in Table 1, the adhesive film prepared by the present invention has a high degree of crosslinking, and will not generate bubbles after long-term aging, thereby avoiding the problem of corrosion of the battery cell by acetic acid precipitation. Specifically, the initial degree of crosslinking of the adhesive film prepared by the present invention is 85.11-89.93%, the degree of crosslinking after storage for 6 months is 81.57-85.03%, the power attenuation after DH1000H is 1.27-1.95%, and the battery cell is good after DH1000H without blackening.
[0080] In Comparative Example 1, dipentaerythritol pentaacrylate was replaced with TAIC. After 6 months of storage, the crosslinking degree decreased significantly and did not meet the requirement of 80%.
[0081] In comparative example 2, no (3,4-epoxycyclohexyl) methyl acrylate was added, and the power attenuation after DH1000H was significantly increased, and the battery cell was corroded and turned black.
[0082] In comparative example 3, methyl acrylate (3,4-epoxycyclohexyl) was replaced with an equal amount of magnesium hydroxide. After DH1000H, the power attenuation was significantly increased, and the battery cell was corroded and turned black.
[0083] The present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0084] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0085] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0086] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A transparent POE white EVA co-extruded film, characterized in that: Including a transparent POE layer and a white EVA layer formed by co-extrusion; The transparent POE layer comprises the following components in parts by weight: POE 97.4-98.9 parts 0.5-1 part of tert-butyl peroxy-2-ethylhexyl carbonate 0.4-0.8 parts of cross-linking agent Silane coupling agent KH570 0.1-0.5 parts Antioxidant 770 0.1-0.3 parts; Wherein, the auxiliary cross-linking agent comprises dipentaerythritol pentaacrylate and / or dipentaerythritol hexaacrylate; The white EVA layer comprises the following components in parts by weight: EVA 86.9-93.0 parts 5-10 parts titanium dioxide 0.5-1 part of tert-butyl peroxy-2-ethylhexyl carbonate Triallyl isocyanurate 0.3-0.8 parts Silane coupling agent KH570 0.1-0.5 parts Antioxidant 770 0.1-0.3 parts 0.1-0.5 parts of epoxy compound with double bond structure; The epoxy compound with a double bond structure comprises 4-vinyl epoxycyclohexane and / or (3,4-epoxycyclohexyl) methyl acrylate.
2. A method for preparing the transparent POE white EVA co-extruded film according to claim 1, characterized in that: The method comprises the following steps: co-extruding POE and EVA according to a ratio, and irradiating the co-extruded film to obtain the transparent POE and white EVA film.
3. The preparation method according to claim 2, characterized in that The energy of the irradiation is 15-35 kgy; The voltage of the irradiation is 300-500 kV; The irradiation speed is 40-60 m / min.
